Human bone: the tissue characteristics determining its mechanical behaviour - Ohman, Anna Maria Caroline <1980> (Alma Mater Studiorum - Università di Bologna, 2011)
The present thesis illustrates the research carried out during the PhD studies in Bioengineering. The research was aimed to characterise the human bone tissue, with particular regard to the differences between cortical and trabecular bone. The bone tissue characteristics that affect its mechanical properties were verified or identified, using an experimental approach, to corroborate or refute hypotheses based on the state of the art in bone tissue biomechanics.